The Criminal Responsibility in Cases of Child Abortion - Darmawan, Agung Wibowo; Octarina, Nynda Fatmawati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study analyzes criminal liability in cases of abortion carried out by minors and considers whether the immature age can be a reason for the elimination of criminal liability. Given that children are in a vulnerable position and often do not understand the legal consequences, social and economic factors such as family pressure, partners, or community stigma also influence their decisions. Using qualitative methods, this study examines legal aspects based on court decisions and regulations in Indonesia and compares legal approaches in other countries. The results of the study show that although children have special legal protection, this does not automatically eliminate criminal liability, except in certain conditions such as coercion or unconsciousness. In many cases, children who have abortions are actually victims of exploitation or sexual violence, so they need protection more than punishment. Therefore, this study emphasizes the importance of legal policy reform that pays more attention to psychological and social aspects, so that the justice system is not only oriented towards punishment, but also towards the restoration and protection of children's rights.